An Analysis of Students’ Computational Thinking Skills on The Number Patterns Lesson during The Covid-19 Pandemic - Dwi Fitriani Rosali; Didi Suryadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
The development of the education curriculum in Indonesia makes students must have skills so that they can compete globally, especially in the 21st century. The development is closely related to technology and information. One of skills that support the development of technology and information is the computational thinking skills. This study aims to analyze students’ computational thinking skills on the number patterns lesson during the Covid-19 pandemic. This study was qualitative-descriptive research with the subjects of 4 students from 8th grade in Makassar. The instruments used in this study were a test of the computational thinking skills in the form of essay type test on the number patterns lesson and interview guidance. The results of this study indicated that all subjects met the first indicator of problem decomposition and one subject met the second indicator of problem decomposition, all subjects met the indicator of pattern recognition, three subjects met the indicator of abstraction and generalization, all subjects met the first indicator of algorithmic thinking and two subjects met the second indicator of algorithmic thinking on computational thinking skills. Thus, students’ computational thinking skills during the Covid-19 pandemic were still low, so an educational framework is needed to improve students’ computational thinking skills.